2023
DOI: 10.1007/s40670-023-01728-9
|View full text |Cite
|
Sign up to set email alerts
|

Student Engagement Using HoloLens Mixed-Reality Technology in Human Anatomy Laboratories for Osteopathic Medical Students: an Instructional Model

Abstract: Mixed-reality technology is a powerful tool used in healthcare and medical education to engage students in life-like scenarios. This blend of virtual and augmented reality images incorporates virtual projections with the real environment to allow real-time observation and interaction [ 1 ]. While this immersive technology offers advantages over cadaver dissections, it creates new challenges to keeping students engaged [ 2 , 3 ]. Student engag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…This model can be adapted for retail, where engaging customers on multiple levels -behaviorally, emotionally, and cognitively -is crucial. The findings suggest that MR technology, when used effectively, can significantly enhance engagement by providing immersive, interactive experiences that resonate with users on various levels (Richards, 2023).…”
Section: Customer Engagement Through Mixed Reality: Strategies and Ou...mentioning
confidence: 92%
See 1 more Smart Citation
“…This model can be adapted for retail, where engaging customers on multiple levels -behaviorally, emotionally, and cognitively -is crucial. The findings suggest that MR technology, when used effectively, can significantly enhance engagement by providing immersive, interactive experiences that resonate with users on various levels (Richards, 2023).…”
Section: Customer Engagement Through Mixed Reality: Strategies and Ou...mentioning
confidence: 92%
“…This study highlights the potential of interactive AI and MR technology in creating engaging retail experiences that not only attract customers but also encourage them to engage more deeply with the brand (Kathikeyan et al, 2022). Richards (2023) presented a case study on the use of HoloLens MR technology in human anatomy laboratories for osteopathic medical students. While this study is set in an educational context, it provides valuable insights into the effectiveness of MR in engaging users.…”
Section: Customer Engagement Through Mixed Reality: Strategies and Ou...mentioning
confidence: 93%
“…Many other studies have found that AR learning enhances learning outcomes compared to conventional methods. This includes increased motivation to learn, higher self-confidence in the acquired abilities, and a greater capacity to apply learned procedures in clinical settings [62], [64], [67]. However, researchers also concluded that AR education tools need further refinement and pre-learning orientation on the use of AR devices, which is necessary for students to properly utilize these tools [65].…”
Section: B Summary Of the Hmd-based Ar Studiesmentioning
confidence: 99%
“…[54]- [57], [62], [63], [66], [68] functionalities, we found that 3 (25%), 4 (33%), 3 (25%), 2 (17%), and 0 (0%) mobile-based applications, as well as 1 (3%), 18 (50%), 10 (28%), 3 (8%), and 4 (11%) HMDbased applications, fell into the 5 categories following the order described above, respectively, as shown in Figure 5a. Among the functionalities, 3D visualization and information display are the two most common reasons that both mobileand HMD-based studies implemented AR technology.…”
Section: Horizontalmentioning
confidence: 99%
“…Additionally, virtual reality (VR) and augmented reality (AR) has been used to create interactive 3D models that allow students to explore the body and its systems in an engaging and immersive way. The integration of these technologies has revolutionized the delivery of medical education and expanded the possibilities for remote learning and digital resources (12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%